Electrical Properties of Polyurethane Graphite Composites - Abd Majid, Wan Haliza (2008)
Polyurethane (PU) is one of the industrially important polymers which offers a combination of unique properties and meets a wide range of demanding application. Electrical conductivity and dielectric properties of polyurethane/graphite composites were investigated in this paper. Moisture Cured Polyurethane was prepared with varying NCO/OH ratio 2.0, 2.2 and 2.4 by polyoxytetramethylene glycol (PTMO) Mw 2000 and Toluene diisocyanate (TDI). Graphite powder of 0 to 12.5 vol% was dispersed in PU to form electro conductive composites. Percolation concentrations were determined to be as (9±1), (9±2) and (10±3) vol. % for the NCO/OH ratio of 2.0, 2.2 and 2.4 respectively. It shows that percolation concentration does not have significant change as the NCO/OH ratio increases. The dielectric properties of the composites were investigated in the frequency range of 1 KHz to 10MHz. It was found that PU composites became electro-conductive when filled with 9 to 10.0% of the filler and support well the dc conductivity results.